HEAD teachers managing entrepreneurship education – Empirical evidence from general education. (April 2016) - Ruskovaara, Elena; Hämäläinen, Minna; Pihkala, Timo
Abstract: The purpose of this paper is to examine the effect of head teachers' background characteristics on the entrepreneurship education of schools. The study analyzes how the background characteristics of head teachers explain the implementation of entrepreneurship education in schools. The methods applied were analysis of variance and linear regression analysis. The data consists of 135 Finnish general education head teachers. The results show that while the head teachers and schools bring out some interesting differences, only the school level and the head teacher's training in entrepreneurship education can help to anticipate entrepreneurship education activities in the school. Highlights: The focus is on the effects of head teachers' background characteristics on schools' entrepreneurship education activities. Head teachers' training in entrepreneurship education (EE) has predictive power on schools' EE activities. Head teachers' gender, business background, and work experience do not explain entrepreneurship education activities. The results of the paper indicate a great need for the development of head teacher training for entrepreneurship education.